Italian adolescents and sexual health: what has changed during the last 20 years?. (13th November 2019) - Kundisova, L; Nante, N; Lorenzini, C; Valeri, V; Messina, G; Alaimo, L
Abstract: Background: In the majority of European countries, sex education is mandatory, but Italy is still an exception. Despite sexually transmitted diseases (STD) are believed to be less common today, long-time "forgotten" disease, as syphilis, are returning. The aims of study are i) to examine the knowledge and perceptions of adolescents regarding sex education and STD and ii) to compare our results with Italian national survey. Methods: This descriptive cross-sectional study was conducted in 6 middle schools in Siena (Italy) during May-June 2018. Data were anonymous collected using a validate questionnaire previously adopted by the Italian National Institute of Health (NIH). The results were compared with the national survey realized in 1998 by NIH. The analysis was performed using Stata 12. Results: From 691 questionnaires, 540 returned fulfilled (78% response rate). The majority (95%) of respondents considered sex education "important" and thought it should be guaranteed by the school; 48% described information received so far as "sufficient", 40% as "adequate". "School" was indicated as the principal source of information (44%), instead of "friends" which resulted in 1998. The respondents were asked to choose from the list the STDs they knew: 96% indicated "AIDS", 62% "syphilis", 38% "HBV" and 36% "gonorrhoea". In comparison to 1998, knowledge of syphilis has decresed (2018:17% vs. 1998:62%) and HBV (2018:38% vs. 1998:58%). Regarding STD, the "mass media" were cited as the principal source of information (56%), followed by "school" (41%) and "General Practitioner" (20%). Conclusions: In comparison to 1998 sex education in Italian schools improved, but the knowledge of adolescents regarding the STD worsened. This result can be attributed to the fact that the survey of 1998 was realized during the years when the AIDS awareness was higher. It is necessary to further improve the sex education in Italy in order to prevent STDs. Key messages: The "forgotten" sexually transmitted diseases are becoming common again, the adequate sex education in schools is necessary to prevent them. In confrontation to 1998, the sex education in Italian schools improved, but the knowledge of adolescents regarding the STD worsened.